Investigating the optoelectronic and thermoelectric nature of IrSbX (X = S, Se, and Te) TMC's semiconductors: By employing the accurate modified Becke-Johnson exchange potential. (15th June 2022) - Salman Khan, Muhammad; Gul, Banat; Ahmad, Bashir; Khan, Gulzar; Khattak, Shaukat Ali; Khan, Tahirzeb; Ajaz, Muhammad; Zulfiqar, Syed; Wahab, Fazal
Abstract: The Iridium-based transition metal chalcogenides display significant results in terms of their optoelectronic and thermoelectric properties are investigated using the accurate Trans-Blaha modified Becke–Johnson potential under the framework of the density functional theory. The stable lattice constant was used to calculate the electronic band structures and density of states. Our calculated results show an indirect bandgap nature because conduction band minima and valance band maxima do not co-exist at the same Г-point symmetry. An increase in the bandgap value i.e., (IrSbS) > (IrSbSe) > (IrSbTe) can be attributed due to a shift linked with conduction bands near the Fermi energy level. The total and partial density of states for the three TMC's were computed, compared, and discussed in detail at different energy ranges. The frequency-dependent linear optical parameters such as the complex dielectric function absorption coefficient, extinction coefficient, reflectivity, refractive index, and the energy loss function are calculated and discussed. These computed results confirm that our studied materials are the most promising materials for optical devices that work in the infrared and visible regions of the solar spectrum. Additionally, the thermoelectric transport parameters like the Seebeck coefficient, thermal conductivity, specific heat capacity, the power factor, and the figure of merit were also computed by using the BoltzTrap code. The computed high specific heat capacity along with power factor value for IrSbTe as compared to the other two materials elucidate and confirm the material to be more efficient at generating or extracting heat energy.